LARYNGEAL MUCORMYCOSIS IN AN UNCONTROLLED DIABETIC PATIENT: A CASE REPORT - Erum Shahzadi; Ali Shayan; Zia-us-Salam Qazi; Sarfraz Latif; Sohail Ahmad Malik; Usman Chaudhary (Journal of Ayub Medical College Abbottabad, 2024)
Background: With rising conditions in immunocompromised states, the world is facing the challenge of fungal infections with mucormycosis which was rare previously. With the rise in diabetic patients, COVID-19-related immunosuppression, and steroid use, along with an increasing number of transplant and chemotherapy patients, there has been a notable surge in mucorales infections. Although patients with rhino-orbit-cerebral mucormycosis are the most common type of pulmonary rare ones. Methods: Here, we are reporting 1st case of laryngeal mucormycosis in a 55-year-old male presented with respiratory distress in the ENT department of Shaikh Zayed Hospital, Lahore. He had a 4-year history of poorly controlled diabetes, with no other identifiable risk factors. An emergency tracheostomy was performed, pus was aspirated, and necrotic tissue was debrided to relieve the airway obstruction. Conclusion: Laryngeal mucormycosis was diagnosed in the subglottic region via multiple biopsies through direct laryngoscopy under anesthesia. The emergence of new variants of mucormycosis is calling for vigilant identification and meticulous control of predisposing risks. Concomitant debridement and intravenous amphotericin B are recommended under current guidelines.